Montgomery Multiplier for Faster Cryptosystems. (2016) - Thampi, Nitha; Jose, Meenu Elizabath
Abstract: With the advancement in communication systems, security is a prime concern which is offered by cryptosystems Modular arithmetic is core operation in most of the cryptosystems. Many cryptosystems including RSA, DSA and ECC systems requires modular multiplication for private key generation. It uses modular exponentiation of large numbers to encrypt data, which is a slow process due to repeated modular multiplications. The efficiency of cryptography systems practically depend on how fast the modular multiplication is done, since these are at the base of computation. Many hardware and software implementations for faster modular multiplication have been proposed, Montgomery Multiplication Algorithm is recognized as the most efficient among these. This paper presents a 32-bit implementation of a Faster Montgomery algorithm for performing modular multiplication. The algorithm is based on the method proposed by Montgomery for modular multiplication and is complementary to the available techniques. Simulation shows that our design performs faster in terms of clock frequency while it requires lower area.